2017
DOI: 10.5603/cj.a2017.0016
|View full text |Cite
|
Sign up to set email alerts
|

A review of the utility of a hypothermia protocol in cardiac arrests due to non-shockable rhythms

Abstract: (Cardiol J 2017; 24, 3: 324-333)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Layperson CPR training is essential to increase bystander CPR rates and OHCA outcome [20]. Moreover, it is worth remembering that teaching how to act in life-threatening situations, including cardiac arrest resulting from myocardial dysfunction or arrhythmias, is a key element of public safety [21]. Although schools are seen as an ideal environment to involve citizens in BLS training, it is not clear however, which professionals are more suitable for teaching schoolchildren [12,14,22].…”
Section: Discussionmentioning
confidence: 99%
“…Layperson CPR training is essential to increase bystander CPR rates and OHCA outcome [20]. Moreover, it is worth remembering that teaching how to act in life-threatening situations, including cardiac arrest resulting from myocardial dysfunction or arrhythmias, is a key element of public safety [21]. Although schools are seen as an ideal environment to involve citizens in BLS training, it is not clear however, which professionals are more suitable for teaching schoolchildren [12,14,22].…”
Section: Discussionmentioning
confidence: 99%
“…Sudden cardiac arrest in pediatric patients is uncommon [1,2]. In newborns, correct ventilation is a key element in cardiopulmonary resuscitation and support of transition at birth but correct chest compression (CC) improves resuscitation quality and thus affects vital organ perfusion, the return of spontaneous circulation, and survival rate [3][4][5][6]. The quality of CC is often suboptimal owing to incorrect CC technique, fatigue, and the rescuer position or experience [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that 60% of out-of-hospital cardiac arrests (OHCA) survivors are treated by emergency medical service personnel, their prognosis is still very poor with survival rates reaching only 9.5% (8.8-10.2%) [1][2][3][4][5]. Two independent, randomized control trials for myocardial infarction patients who had OHCA confirmed an improvement in survival and neurological outcomes resulting from the application of mild therapeutic hypothermia (MTH) [6,7].…”
Section: Introductionmentioning
confidence: 99%